Abundance and phenotypic-genotypic analysis of antibiotic-resistant Escherichia coli isolated from wastewater of the Zainoel Abidin Hospital, Banda Aceh, Indonesia - NOVEKHANA ANELIA; SUHARTONO SUHARTONO; ZINATUL HAYATI (Society for Indonesian Biodiversity, 2023)
Abstract. Anelia N, Suhartono S, Hayati Z. 2023. Abundance and phenotypic-genotypic analysis of antibiotic-resistant Escherichia coli isolated from wastewater of the Zainoel Abidin Hospital, Banda Aceh, Indonesia. Biodiversitas 24: 2294-2301. Excessive and inappropriate use of antibiotics can initiate the emergence of antibiotic resistance in bacteria. Wastewater Treatment Plant (WWTP) is believed to be a reservoir for antibiotic-resistant bacteria, including Escherichia coli. This study aimed to perform the enumeration, isolation, characterization, and evaluation of resistance properties and antibiotic resistance-coding genes encoded by a plasmid of E. coli isolates from WWTP of the dr. Zainoel Abidin General Hospital (RSUDZA). The study was conducted through several stages, including the isolation and quantification of E. coli, antibiotic resistance testing, confirmation testing of ESBL-E. coli isolates, isolation of plasmid DNA, and amplification of TEM, SHV, and CTX-M genes. The results showed that the wastewater in the sum pit tank, aeration tank, and final tank of the WWTP contained E. coli at 7.5x104 CFU/mL, 3x102 CFU/mL, and 1x102 CFU/mL, respectively. A total of 22 isolates were obtained, with ten isolates from the sum pit tank, seven from the aeration tank, and five from the final tank. Escherichia coli isolates had resistance to eight types of antibiotics in the aeration tank and seven types in the final tank, compared to the sum pit tank of the WWTP. Therefore, 59% of the isolates were classified as Multi-drug Resistant (MDR) and 32% as Extended Spectrum ?-Lactamase E. coli (ESBL-EC). TEM, SHV, and CTX-M genes were detected in all locations at 63.6%, 22.7%, and 95.5%, respectively. In addition, CTX-M was the most common gene found in wastewater isolates at RSUDZA WWTP. The hospital wastewater treatment process must be improved to reduce the presence of antibiotic-resistant bacteria and the spread of antibiotic resistance genes.